Multivariate analyses of water quality indices and incidence of Aeromonas species in water from different holding facilities in Kwara State, Nigeria - Deborah Arimie Adah; Lawal Saidu; Sonnie Joshua Oniye; Moshood Abiola Raji; Adakole Sylvanus Adah; Oluwafemi Babatunde Daodu; Omodolapo Morohunranti Obisesan (BMC Veterinary Research)
Abstract Background This study evaluated the impact and correlation of physiochemical parameters of water from various culture environments on the prevalence of Aeromonas species. The physicochemical parameters of water samples obtained from 36 farms, which included earthen ponds, plastic tanks, and concrete tanks were analysed. The isolated Aeromonas species were further characterised biochemically and molecularly employing the 16s rRNA polymerase chain reaction. Results The monthly count of the presumptive Aeromonas species varied from the different culture facilities and ranged between the least value of 0.2 ± 0.1 × 101 observed in plastic tanks and the highest value of 7.2 ± 0.1 × 105 CFU per 100 ml in earthen ponds and was significantly different at P < 0.05. There were variations in each of the assessed physicochemical parameters of the water from the fish farms and the values of ammonia (1.1 mg/l), nitrite (1.2 mg/l), nitrate (96 mg/l), biochemical oxygen demand (4.2 mg/l), and chemical oxygen demand (19.6 mg/l) were not within the acceptable limit. Except for ammonia, nitrite, and biochemical oxygen demand in concrete ponds and plastic tanks, all the parameters exhibited a positive correlation with each other. The relationship between the parameters and Aeromonas species across the various culture facilities showed positive correlations with pH, dissolved oxygen, nitrite, and biochemical oxygen demand; conversely, temperature, nitrate, carbon dioxide, chemical oxygen demand, and ammonia showed a negative association that influenced the prevalence of Aeromonas species. Conclusion The quality of water in aquaculture plays a critical role in determining fish health, growth, and overall production levels, with poor conditions potentially leading to financial losses. Therefore, it is imperative to maintain and monitor optimal water quality, as it directly influences fish survival, growth rates, and their resistance against diseases.